KONTEN MENARIK, TRAFIK MENINGKAT ( STUDI PENGARUH KONTEN MEDIA TERHADAP KUNJUNGAN AKUN PERUSAHAAN XYZ BANDUNG ) - Pratama Lifianto, Panji; Handayani, Norlia; Agustin, Cahyadi; Surahman, Roni; Nulhakim, Lukman (POLITEKNIK PIKSI GANESHA, 2025)
This study aims to analyze the impact of social media content types on the traffic and engagement of the XYZ company account in Bandung. Using a quantitative approach and a quasi-experimental design, this research involved 100 respondents actively interacting with the company's account. Data were collected through analysis of social media analytics tools such as Google Analytics and Instagram Insights, along with audience surveys. The results revealed that visual content, particularly videos and images, led to a 30% increase in traffic and a 40% increase in engagement compared to text-based content. Furthermore, video content garnered the highest interaction rates, with a significant preference from the audience. Based on these findings, it is recommended that XYZ company focus more on creating visual content that resonates with the audience, utilize analytics tools for performance monitoring, and optimize content strategies across suitable platforms to enhance conversion rates and achieve business goals. This study provides valuable insights for companies in designing more effective and data-driven social media marketing strategies.